Periodontitis and dental quality of life predict long-term survival in head and neck cancer - Mirna Farran; Evelyn Neppelberg; Sigbjørn Løes; Anne K. H. Aarstad; Svein Erik Moe; Hans Jørgen Aarstad (BMC, 2024)
Abstract Background Our aim was to investigate oral health in newly diagnosed head and neck squamous cell carcinoma (HNSCC) patients in relation to long-term survival. We assessed whether the level of alveolar bone loss due to periodontitis at diagnosis, measured from orthopantomogram (OPG), and reported dental health-related quality of life (HRQoL) scores obtained at diagnosis contain prognostic information for HNSCC patients. Methods A total of 79 patients from a consecutive cohort of 106 diagnosed with HNSCC between November 2002 and June 2005 were included. All patients reported dental HRQoL, OPG-determined alveolar bone loss were measured in 79 patients at diagnosis. Reduced alveolar bone loss (≥ 4 mm) from cement-enamel junction on at least two molars or premolars registered both horizontally and vertically served as indicator of periodontal disease. Results With alveolar bone loss, we determined increased mortality by univariate analysis (RR = 2.28, CI: 1.22-4.28, p = 0.01) and a strong trend by multivariate analyses adjusted for standard clinical information (RR = 1.95, CI: 0.98-3.87, p = 0.056). Reported lowered dental HRQoL scores predicted long-term survival in both univariate (RR = 3.58, CI: 1.99-6.45, p < 0.001) and multivariate adjusted for standard clinical information (RR = 2.17, CI: 1.17-4.01, p = 0.014). When analyzed with Cox regression, including alveolar bone loss and dental HRQoL, both factors, adjusted by clinical variables, were significant predictors of long-term survival: dental HRQoL (p = 0.007) and present alveolar bone loss (p = 0.034). Non-HNSCC disease-specific long-term survival predicted was also predicted when alveolar bone loss and dental HRQoL were analyzed simultaneously and adjusted for standard clinical information. Conclusions The degree of alveolar bone loss, as determined by OPG, and dental HRQoL both obtained at the time of HNSCC diagnosis, predicted long-term survival. When analyzed simultaneously, both factors remained significant in both univariate and multivariate analyses, adjusted by pertinent clinical variables, highlighting their unique prognostic value.